147k views
1 vote
6 out of 11 = 29 out of

User Tommizzle
by
4.2k points

1 Answer

4 votes

6 out of 11 = 29 out of ???

We shall start by representing the ??? with letter y.

This means 6 out of 11 = 29 out of y

We can simplify the left hand side to become

6 out of 11 = 5

That means 5 = 29 out of y

Simplify the right hand side to become

29 out of y = y - 29

Therefore,

5 = y - 29

We now have an equation

Add 29 to both sides of the equation (to eliminate the -29 on the right hand side)

5 + 29 = y - 29 + 29

34 = y

So the expression now becomes;

6 out of 11 = 29 out of 34

User Muthurathinam
by
5.4k points